Conceptional Reconstruction of High School English Teaching from the Perspective of Deep Learning - Yi, Zhang (Pacific International Journal, 2023)
As one of the important subjects in senior high school, English is not only a tool for communication, but also has rich cultural significance. High school English teaching should not only make students realize its instrumental significance, but also connect English with social life to guide students to establish correct values and achieve all-round development. The new college entrance examination reform puts more emphasis on competence education and the overall development of students. Meanwhile, the examination-oriented education in senior high school English teaching is still outstanding, and theory of "focus only on scores" is still prevalent. The theories of senior high school English teaching lag behind the development of the times and the call of the country. Deep learning emphasizes the acquisition of students’ English ability, attaches importance to the cultivation of students’ values, and supports the comprehensive development of students, which is complementary to course education. It also has enlightening significance for the reform of English teaching in senior high schools. The paper focuses upon the conceptional reconstruction of senior high school English teaching through the perspective of deep learning theory, and discusses the positive impact of deep learning on the improvement of senior high school students’ English learning initiative, the accumulation of humanistic quality and the formation of values.